Retinopathy of Prematurity (ROP) a Cross-Sectional Study in Basra 2022-2023 - Lubna Abdul Kareem Habib Aleiada; Farah Mohammed Habeeb Al-Jumaah (American Journal of Biomedicine and Pharmacy, 2025)
Preterm labor is characterized by the commencement of labor before reaching 37 weeks of pregnancy based on gestational age: "extremely preterm" for births before 28 weeks, "very preterm" for births between 28 and 32 weeks, and "moderate to late preterm" for births occurring between 32 and 37 weeks. One complication of preterm which is very important is ROP. because it effect on quality of life is a primary contributor to preventable blindness in children. It is a multifaceted condition that affects premature infants, partly caused by incomplete or abnormal development of retinal blood vessels. Worldwide, approximately 50,000 children under 15 are affected by blindness due to ROP-related complications. Aim of the study To assess the presence of ROP in premature neonate. 2- Study the presence of ROP in relation to some neonatal characteristics. In this study we follow up preterm babies after discharge from intensive care unit and send them for ophthalmology from October 2022_october2023 total preterm 77 was male 62. 1% & 47was girl 37.9% total 124 preterm . Most preterm patients suffering from ROP in the study patient less than wight 1000 gram 3. 2% and preterm those need more than 1 week duration of admission in neonatal word. Larger scale study (national) is needed with a larger study group sample. With more detailed assessment of the neonatal course and the timing of screening and assesment for the ROP. Try to implement neonatal screening programs to assist in early detection of ROP and prevent blindness. Help to provide a screening criteria that is more fit for Iraq. Provide the instruments and the training needed for the doctors in the hospitals were neonatal care units are present to facilitate the screening of neonates before discharge.